Evaluasi Program Reading Camp sebagai Upaya Peningkatan Literasi Siswa di SDI Bertingkat Oepura 4 dengan Model Formatif dan Sumatif - Lianti Kann; Anggita Sae; Neci Sitri tameon; Samuel Radja; Yonatan Foeh (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to evaluate the Reading Camp program as an effort to improve students’ reading literacy at SDI Bertingkat Oepura 4 by employing formative and summative evaluation models. The Reading Camp is implemented routinely through engaging methods and is differentiated according to students’ reading proficiency levels. A qualitative-descriptive approach was used, with data gathered via interviews and documentation. Results show that the Reading Camp enhances reading skills, enriches vocabulary, and fosters students’ writing abilities and critical thinking. Active student participation and supporting facilities such as reading corners were found to play a crucial role in nurturing reading interest. Challenges identified include a decline in reading ability after long breaks and students’ lack of confidence when joining groups at different levels. Formative evaluation supports process improvement, while summative evaluation confirms the program’s effectiveness in achieving its objectives. The study underscores the need for sustained literacy strategies, improved learning resources, and ongoing teacher training to optimize literacy programs in elementary schools.